A perception study on China's media engagement in Kenya: from media presence to power influence?. Issue 1 (2nd January 2016) - Zhang, Yanqiu; Mwangi, Jane Muthoni
Abstract : In recent years, China has made tremendous efforts to increase its soft power in Africa by expanding the presence of its media on this continent. The objective of this study is to determine the effects of Chinese media in Africa by examining public perceptions of its presence in Kenya, especially with regard to the audience's knowledge about CCTV Africa and China Daily . Against the backdrop of scholarly criticism, the study focuses on the issues of independence and the credibility of Chinese media in Africa. The findings showed that Chinese media in general helped to promote the public's understanding of China, and their role was viewed as providing an alternative channel of information with potential benefits for Sino–Kenyan relations. However, the findings also showed that the engagement of Chinese media as a soft power in Kenya has not yet shown the intended effects. Both the awareness and influence of the Chinese media in Kenya are limited compared to the dominance of Western media. Therefore, Chinese media should consider a balanced strategy to achieve a favorable influence in Africa by addressing the challenges of Chinese journalistic stereotypes, the African free media environment, and reasonable narrative approaches.